LA TRAJECTOIRE POLITIQUE DE LAURENT- DESIRE KABILA - LOFETU, Pierre BOFENDA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Laurent- Désiré Kabila was at a time a chief of war and a man of state. Arrived to the power following the military victory of the Alliance of the Democratic Strengths for the Liberation of Congo (AFDL), on the troops of Mobutu May 17, 1997, Laurent- Désiré Kabila wanted to institute in DRC a socialist inspiration democracy. For him, the military victory in her only was not sufficient to change Congo. It is why, he extolled what he qualified of" revolution forgiveness ". In his understanding, it was necessary to mobilize the people in its whole to free the country of the neo-colonialism. It could be only possible if the power was really restored to the people through what it called" Committees of popular power ".